Dynamics of agroforestry systems with socioeconomic and environmental changes: case of nipo-paraense cooperatives from the cooperativa agrícola mixed cooperative of Tomé-Açu, Para State (Research, Society and Development, 2022)
The great dilemma in agriculture in the face of socio-environmental problems is to achieve the rationalization of the dynamic production process through the incorporation of new technologies, reduction of production costs (maintaining desirable levels of productivity) and reduction of environmental impacts, combined with the generation of greater social benefits. The main objective of this study is to evaluate the dynamics of the agroforestry systems of the mixed cooperative of Tomé-Açu in the period from 1974 to 2020. The production data and production value were obtained through the SIDRA platform and on the Census of Agriculture 2017. The crops analyzed in the present study are açaí, acerola, cocoa, cupuaçuzeiro, passion fruit, black pepper and dragon fruit. Another means of data collection was the Annual Reports of the Cooperativa Agrícola Mista de Tomé-Açu, more specifically, evaluating the   period from 1974 to 2020, based on these data, the behavior of the percentage of the production value was analyzed, in other words, how much in percentage each specie contributed to the cooperative's total income in a given year. For data analysis, Microsoft Office Excel 2019 software was used for the preparation of tables. In addition, line graphs to better represent the behavior of percentage over time.